Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21. Issue 21 (1st November 2016) - Fu, Shuna; Wang, Fan; Li, Hongyu; Bao, Yixuan; Yang, Yu; Shen, Huifang; Lin, Birun; Zhou, Guangxiong
Abstract: A new secondary metabolite, (2 S, 3 R )-l -threonine, N -[3-(formylamino)-2-hydroxybenzoyl]-ethyl ester (streptomyceamide C, 1 ), together with four known compounds 1, 4-dimethyl-3-isopropyl-2, 5-piperidinedione (2 ), cyclo-(( S )-Pro-8- hydroxy-( R )-Ile (3 ), cyclo-(( S )-Pro-( R )-Leu (4 ), and seco-(( S )-Pro-( R )-Val) (5 ), were isolated from the EtOH extract of the fermented mycelium of the marine-derived streptomycete strain H74-21, which was isolated from sea sediment in a mangrove site. The structure of the new compound was established on the basis of its spectroscopic data, including 1D and 2D NMR, HR-TOF-MS. Their antifungal activities against Candida albicans and cytotoxicities against human breast adenocarcinoma cell line MCF-7, human glioblastoma cell line SF-268 and human lung cancer cell line NCI-H460 were tested. Compounds1 only displayed cytotoxicity against human breast adenocarcinoma cell line MCF-7 with the IC50 value of 27.0 μg/mL. However, compounds1 –5 do not show antifungal activities at the test concentration of 1 mg/mL, and2 –5 have no cytotoxicities at the test concentration of 50 μg/mL. Abstract :